Engineering of Yarrowia lipolytica lipase Lip8p by circular permutation to alter substrate and temperature characteristics. (1st May 2014) - Sheng, Jun; Ji, X F; Wang, F; Sun, M
Abstract: Applications of lipases are mainly based on their catalytic efficiency and substrate specificity. In this study, circular permutation (CP), an unconventional protein engineering technique, was employed to acquire active mutants of Yarrowia lipolytica lipase Lip8p. A total of 21 mutant lipases exhibited significant shifts in substrate specificity. Cp128, the most active enzyme mutant, showed higher catalytic activity (14.5-fold) and higher affinity (4.6-fold) (decreased K m ) to p -nitrophenyl-myristate ( p NP-C14 ) than wild type (WT). Based on the three-dimensional (3D) structure model of the Lip8p, we found that most of the functional mutation occurred in the surface-exposed loop region in close proximity to the lid domain (S112–F122), which implies the steric effect of the lid on lipase activity and substrate specificity. The temperature properties of Cp128 were also investigated. In contrast to the optimal temperature of 45 °C for the WT enzyme, Cp128 exhibited the maximal activity at 37 °C. But it is noteworthy that there is no change in thermostability.